Strengthening National Identity Through Civic Education for Young Children: a Case Study of Indonesia - Rizkiyani, Fanny (International Journal of Engineering and Technology, 2018)
In the globalization era, individuals from one culture can easily access or be exposed to other cultures, or interact with people from different cultures, resulting in cultural exchanges. These interactions may also change the individualsâ€™ identity, including their social identities such as national identity. Therefore, globalization is often seen as the cause of national identity crisis. The author proposes that a good civic education, as early as in the early childhood education, is one of the alternatives in countering the unwanted outcome of globalization, specifically with regards to the construction of national identity. In this article, the author describes how the civic education is incorporated in the early childhood education curriculum in Indonesia. The author also discusses how the civic education curriculum may be improved by using the internet that is once deemed as a threat to the national identity, as the instructional media.Â Â